Quaternary ontogeny of a pampean ‘laguna’ - Dangavs, Nauris Vitauts (1994)
Our sedimentological study of Lobos Lake sediments has shown that, below modern deposits, there is a clastic and biological record of three different paleoenvironments: two aquatic (freshwater and mixohaline respectively) and one subaereal. This record documents the climatic and geomorphologic changes that affected the basin during its evolution up to its present water level, from the upper Pleistocene to the Holocene.